Investigations on dry sliding wear behavior of in situ casted AA7075–TiC metal matrix composites by using Taguchi technique - Baskaran, S.; Anandakrishnan, V.; Duraiselvam, Muthukannan (Materials in engineering, 2014)
[Display omitted] •The AA7075–TiC metal matrix composites were produced by in situ casting technique.•The produced composites were characterized by XRD analysis and SEM.•The dry sliding wear behavior of composites was investigated by Taguchi technique.•The significant factors and their contribution in wear rate identified by ANOVA.•The formation of oxidation at high sliding velocity was verified by EDS. High strength 7075 aluminum matrix composites with 4 and 8wt.% of TiC particulate reinforcement was synthesized by reactive in situ casting technique. X-ray diffraction analysis and scanning electron microscopy were used to confirm the presence of TiC particles and its uniform distribution over the aluminum matrix. The dry sliding wear behavior of the as-casted composites was investigated based on Taguchi L27 orthogonal array experimental design to examine the significance of reinforcement quantity, load, sliding velocity and sliding distance on wear rate. The combination of 4wt.% of TiC, 9.81N load, 3m/s sliding velocity and 1500m sliding distance was identified as the optimum blend for minimum wear rate using the main effect plot. Load and sliding velocity were identified as the highly contributing significant parameters on the wear rate using ANOVA analysis. Further a confirmation test was also conducted with the optimum parameter combination for validation of the Taguchi results.